Business cycle and innovation activity in medium-high and high technology industry in Poland = Koniunktura gospodarcza a aktywność innowacyjna systemów przemysłowych średnio-wysokiej i wysokiej techniki w Polsce - Dzikowski, Piotr (Zielona Góra: Faculty of Economics and Management Press)
This article examines differences in an impact of business cycle phases on innovation activity in medium-high and high technology industry in Poland. It is assumed that each business cycle phase influences innovation activity in the same fashion, but its impact varies and it depends on the firm?s innovation activity. The higher innovation activity the less impact of business cycle.
Keywords: innowacja; cykl koniunkturalny; przemysł; MHT; HT; wysoka technika; innovation; business cycle; industry; high technology